Dari Karyawan Menjadi Wirausahawan: Sebuah Analisis Kualitatif Guncangan Karier pada Wirausahawan Milenial - Ebnu Halim; Chandra Fitra Arifianto (STKIP PGRI SITUBONDO, 2023)
Not all employees will immediately succeed in pursuing a career as an entrepreneur. There are several shocks that can discourage you from switching careers as an entrepreneur. Therefore, this study aims to describe career shocks (consisting of: career choice, career development, and career adaptation) experienced by millennial entrepreneurs when they switch careers from employees to entrepreneurs. This study uses qualitative methods with observation, interviews, and documentation, as data collection techniques. Data reduction was carried out to get the meaning of the informants' answers. This meaning will be aligned to obtain an explanation of the research questions. For this reason, this study used 5 (five) informants who are millennial entrepreneurs, choosing to switch careers from employees to entrepreneurs and domiciled in Tangerang City. The results of the study show that facing career shocks as an entrepreneur requires capital and mentality when choosing a career, skills and performance strategies that can be obtained from experience while being an employee to develop a career, and self-management by making standard adjustments to adapt.